Ionoelastomer material with improved ion mobility, diode device including the same, logic gate controlled by light using the same, and device controlled by light including the same
Patent Information
- Application Number
- KR1020250023456
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2026-09-01
Smart Images

Figure PAT00007_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a composite ion elastomer material with improved ion mobility, a diode device including the same, a logic gate whose characteristics are controlled by light using the same, and a light control device including the same. Background Technology
[0002] Advancements in ionotronics require high-performance ion-conducting materials that enable diverse applications such as biomarkers, energy storage, human-machine interfaces, soft robotics, and bionic prosthetics. Most stretchable ion conductors (e.g., salt-dissolved hydrogels, polymer gels expanded with ionic liquids, and polyelectrolytes composed of positively or negatively charged polymer networks) possess advantages such as intrinsic stretchability, optical transparency, and biocompatibility. These characteristics are benefits that are difficult to achieve with conventional electronic conductors. Ion conductors have expanded their scope of application to new ionotronic devices for artificial muscles, skin-like displays, artificial axons, stretchable touchpads, thermometers, and thermoelectric batteries.
[0003] An ion junction was formed by physically stacking an ion conductor (p-type) that induces the preferential movement of cations and an ion conductor (n-type) that induces the preferential movement of anions. This induces unique ion rectification characteristics similar to electronic pn junctions. Successful ion current rectification and switching have been demonstrated in various gel-based materials. These include water-soluble polyelectrolytes in which positively or negatively charged ions exist within polymer networks, hydrogels containing dissolved salts, organic hydrogels, bipolar membranes, charged nanochannels, and materials involving metal-electrolyte redox reactions. This demonstrates potential suitable for applications such as biosensors, soft generators, and ion logic circuits. However, most existing ion devices cannot avoid performance degradation due to solvent leakage and evaporation.
[0004] Recently, solvent-free ionoelastomers have garnered attention due to their solvent-free nature and excellent environmental stability. However, most solvent-free ionoelastomers are susceptible to ion leakage because they are synthesized with lithium salts or dipolar ions dissolved in the elastomer matrix. In particular, mobile ions in ionoelastomers easily diffuse when in contact with other ionoelastomers due to ion concentration gradients. On the other hand, polyelectrolytes in which a charged polymer main chain is ionically bonded to a mobile counterion provide excellent mechanical properties and minimal solvent and ion leakage. Furthermore, their selective ion transport characteristics enable a wide range of solid-state ion junction devices. These devices exhibit superior ion current rectification. To expand the application range of solid-state ion junction devices, there is a need to develop ion-elastomer junctions with ion current rectification characteristics that respond reversibly to external stimuli such as mechanical pressure, temperature, light, and humidity. To achieve this, stimulus-responsive ion junctions must be designed by introducing stimulus-responsive fillers into the ionoelastomer to enhance rectification performance.
[0005] Two-dimensional nanosheets (MXene, Ti3C2T x MXene possesses high electrical conductivity, a large surface area, and abundant hydrophilic surface functional groups, and exhibits excellent photothermal conversion properties. These characteristics enable various applications such as sensors, energy storage / harvesting devices, electromagnetic interference shielding components, and biopharmaceuticals. Hydrophilic MXene nanosheets are expected to be easily integrated into ionic elastomers, and the photothermal properties of MXene enable temperature-sensitive ion rectification at ion junctions.
[0006] Here, we propose a NIR (Near-Infrared) responsive ion junction and implemented a reconfigurable logic gate using it. A bilayer ion junction was formed by stacking a p-type polyelectrolyte ion elastomer containing MXene nanosheets with a positive surface potential and an n-type polyelectrolyte ion elastomer containing MXene nanosheets with a negative surface potential. This device is positioned between embedded flexible liquid metal electrodes and provides a NIR responsive ion junction device. The surface potential-controlled MXene nanosheets contained in the ion elastomers promoted the diffusion of mobile ions bound to the polyelectrolyte main chain, thereby enhancing the rectification performance of the ion junction. Upon exposure to NIR radiation, the rectification performance was further improved as the device temperature rose due to the NIR-thermal energy conversion of the MXene nanosheets. By manipulating the rectification ratio of the ion junction with the NIR exposure time and output, we demonstrated a novel reconfigurable ion logic gate. This logic gate reversibly performs a logic transition from AND to OR through NIR exposure and device cooling processes in a device with two ion junctions connected in series. The problem to be solved
[0007] The problem that the present invention aims to solve is to overcome the solvent leakage and environmental instability of existing ion conductors and to develop a material with higher ion mobility. To this end, a composite ion elastomer material is created by mixing an ion elastomer with a charged MXene, and diode devices and optical control devices using this material are proposed. This approach can improve ion conductivity, increase stability, and help control the characteristics of logic gates using light. means of solving the problem
[0008] In one aspect, the present invention provides a composite ion-elastomer material with enhanced ion mobility comprising: an ion-elastomer; and a positively or negatively charged MXene contained within the ion-elastomer that interacts with one of a cation or anion.
[0009] In one embodiment, the mobility of ions having the same charge as MXene in the ion elastomer can be improved.
[0010] In one embodiment, the ionic elastomer may comprise one or more materials selected from the group comprising 1-ethyl-3-methylimidazoliium (3-sulfopropyl) acrylate ([EMIM][SPA]) and 1-[2-acrylooxyethyl]-3-butylimidazoliium bis(trifluoromethane)sulfonamide ([AEBI][TFSI]).
[0011] In one embodiment, the MXene is Ti3C2T x , and Ti3C2T with surfaces treated with polyethyleneimine (PEI) x It may include one or more substances selected from the group including
[0012] In another aspect, the present invention provides an ion elastomer-based diode device with improved ion mobility, comprising: an n-side comprising an ion elastomer; and a negatively charged MXene interacting with a cation contained within the ion elastomer; and a p-side in contact with the n-side comprising an ion elastomer; and a positively charged MXene interacting with an anion contained within the ion elastomer.
[0013] In one embodiment, the diode element may further include a first electrode in contact with the n-side; and a second electrode spaced apart from the first electrode and in contact with the p-side.
[0014] In one embodiment, the ionic elastomer of the n-side may comprise one or more materials selected from the group including 1-[2-acrylooxyethyl]-3-butylimidazoliium bis(trifluoromethane)sulfonamide ([AEBI][TFSI]).
[0015] In one embodiment, the ionic elastomer of the p-side may comprise one or more materials selected from the group including 1-ethyl-3-methylimidazolium (3-sulfopropyl) acrylate ([EMIM][SPA]).
[0016] In one embodiment, the MXene included in the n-side is Ti3C2T x It may include one or more substances selected from the group including
[0017] In one embodiment, the MXene included in the p-side is Ti3C2T with a surface treated with polyethyleneimine (PEI). x It may include one or more substances selected from the group including
[0018] In one embodiment, the MXene included in the n-side or the p-side may be included in an amount of about 0.5 to 3 wt%.
[0019] In another aspect, the present invention provides a logic gate whose characteristics are controlled by light, comprising a diode element including: an n-side comprising an ion elastomer; and a negatively charged MXene interacting with a cation contained in the ion elastomer; and a p-side in contact with the n-side, comprising an ion elastomer; and a positively charged MXene interacting with an anion contained in the ion elastomer; and further comprising: two or more input electrodes in contact with one side of the n-side or the p-side; and an output electrode spaced apart from the input electrode and in contact with the other side.
[0020] In one embodiment, the diode element may include an ion-elastomer-based diode element with enhanced ion mobility according to the embodiment of the present invention described above.
[0021] In one embodiment, when light is irradiated, the resistance of the diode element may be lowered.
[0022] In another aspect, the present invention provides a light control element comprising: a gate whose characteristics are controlled by light; and a light source capable of irradiating light to the gate.
[0023] In one embodiment, the gate may include a gate according to the embodiment of the present invention described above.
[0024] Although the development of ion junctions composed of two types of ion conductors for ion current rectification has achieved significant progress comparable to electronic p-type and n-type junctions, stimulus-responsive ion junctions capable of reversibly controlling rectification characteristics by stimulation are rarely reported. The present invention presents a near-infrared (NIR) responsive ion junction and an application utilizing it as a reconfigurable logic gate. The NIR responsive ion junction consists of four vertically stacked components: a bottom liquid metal electrode, a bilayer composed of two types of ion-conducting elastomers (ion carriers) (an ion conductor that does not contain liquid through which ions can move, containing cations (p-type) and anions (n-type)), and a NIR responsive MXene (Ti3C2T x ) 2D nanosheets are mixed), and the liquid metal electrode on top.
[0025] The research results revealed that incorporating two types of MXene nanosheets, each possessing positive and negative surface potentials, into cation- and anion-conducting elastomers promotes the diffusion of mobile ions. This resulted in an improvement in the current rectification characteristics of the ion diode. More importantly, it was confirmed that the rectification characteristics of the ion junction are further enhanced upon exposure to NIR due to the temperature rise caused by the photothermal energy conversion of the MXene nanosheets. Based on the ability to easily control the rectification ratio by controlling the exposure time and intensity of NIR, a novel reconfigurable ion logic gate was developed. In this invention, it was demonstrated that by connecting two ion junctions in series, the transition from an AND gate to an OR gate can be reversibly controlled through NIR exposure and device cooling processes. The NIR-responsive ion junction and logic gate applications presented in this invention offer innovative possibilities that overcome the limitations of existing ion conductor-based technologies. Effects of the invention
[0026] The effect of the present invention is to enhance the performance of diode devices by improving ion conductivity. This enables more efficient electronic device design and opens up the possibility of utilization in various application fields. In particular, in the case of light control devices, characteristics can be controlled by external light, allowing for greater flexibility compared to existing devices with fixed characteristics. This can lead to innovative technological advancements in the development of next-generation electronic devices or wearable devices, and further contribute to the realization of high-performance devices capable of operating stably in various environments. Brief explanation of the drawing
[0027] Fig. 1. Ionic elastomer, charged MXene, ionic elastomer-MXene complex. (a) Schematic of n-type ionic elastomer (AT) and p-type ionic elastomer (ES). Additional schematic of negatively charged MXene (NMXene) and positively charged MXene (PMXene), which exhibit functional groups with negative and positive dipoles. The ionic elastomer is mixed with the charged MXene to form AT-NMXene and ES-PMXene complexes. (b) SEM image of NMXene and PMXene on an anodic aluminum oxide (AAO) film. TEM image showing the 2D structure of NMXene and PMXene. (c) FT-IR data of NMXene and PMXene. (d) Zeta potential of NMXene and PMXene. (e) XRD pattern of NMXene and PMXene showing the spacing between MXene layers (002 peak). (f) Photographs of AT-NMXene and ES-PMXene. (g) XRD patterns of AT, AT-NMXene, ES, and ES-PMXene. (h) DSC data of AT, AT-NMXene, ES, and ES-PMXene. (i) Stress-strain curves of AT, AT-NMXene, ES, and ES-PMXene according to various charge particle weight ratios. Fig. 2. Ionic properties of ion-elastomer-MXene complexes. (a) Nyquist plot for AT-NMXene / AT-NMXene homozygosity (as a function of AT-MXene). (b) Nyquist plot for ES-PMXene / ES-PMXene homozygosity (as a function of ES-MXene). (c) Ratio of integrated regions of XPS results corresponding to mobile anions (TFSI-) in AT or AT-NMXene. (d) Ratio of integrated regions of XPS results corresponding to mobile cations (EMIM+) in ES or ES-PMXene. (e) Diffusion coefficient of TFSI- in AT or AT-NMXene using 19F-NMR. (f) Diffusion coefficient of EMIM+ in ES or ES-PMXene using 1H-NMR. (g) Schematic illustration showing the increase in mobile ions as a result of ion-dipole interactions in AT-NMXene. (h) Schematic illustration showing the increase in mobile ions as a result of ion-dipole interactions in ES-PMXene. Fig. 3. Diode performance and ionic characteristics of a heterojunction diode. (a) Schematic of current rectification by an ES-PMXene / AT-NMXene junction. (b) Diode operation mechanism under reverse and forward bias. (c) Nyquist plot of an ES-PMXene / AT-NMXene (1 wt%) junction as a function of DC bias in AC impedance measurements. (d) Bode phase plot. (e) Current density of an ES-PMXene / AT-NMXene junction under various forward and reverse biases. (f) Nyquist plot of an ES-PMXene / AT-NMXene junction according to various PMXene or NMXene contents (0 wt%, 0.5 wt%, 1 wt%, 3 wt%). (g) Impedance plot. (h) Frequency-capacitance curve. (i) Current density of an ES-PMXene / AT-NMXene junction under forward and reverse biases according to various MXene contents. (j) Rectification ratio of the junction diode. (k) QV curve as a function of MXene when ±0.4V is applied. Fig. 4. Near-infrared (NIR) responsive ES-PMXene / AT-NMXene heterojunction diode. (a) Schematic of a NIR responsive ES-PMXene / AT-NMXene heterojunction diode based on the photothermal effect of MXene within the junction. 400 mW / cm² 2 (b) Photograph of the temperature change of the ES-PMXene / AT-NMXene junction when NIR is applied. (c) UV-VIS-NIR spectra of ES, ES-PMXene, AT, and AT-NMXene. (d) Temperature change of the ES-PMXene / AT-NMXene junction as a function of NIR output. (e) Nyquist plot of the ES-PMXene / AT-NMXene junction as a function of NIR output. (f) Relative rectification ratio as a function of NIR output. The relative rectification ratio is the value divided by the rectification ratio in the absence of NIR. (g) QV curve of the ES-PMXene / AT-NMXene diode with and without NIR exposure. Fig. 5. Reconfigurable ion logic gate using NIR reactive junction diodes. (a) Ion logic gate with two ion diodes and one large resistor connected in series. Electrode configuration of the logic gate circuit composed of ES-PMXene and AT-NMXene. (b) Reconfigurable ion logic gate heated by the photothermal effect. The ion logic circuit switches from an AND gate to an OR gate under NIR illumination. (c) Output current corresponding to the input signal. As the logic gate heats up, the current increases and it operates as an OR gate. Upon cooling, it switches back to an AND gate. (d) 400 mW / cm² 2(e) Change in output current when NIR is applied and a cycle repeated 10 times. (f) Output voltage of the logic gate when NIR is turned on and off using a resistor on the output line. (f) Schematic of the circuit connecting the Arduino and the ion logic gate. The Arduino is programmed to turn on the LED when the output voltage of the ion logic gate exceeds a threshold. When the ion logic circuit switches from an AND gate to an OR gate under NIR illumination, the output value becomes '1' for the signal (1,0) or (0,1), and the LED turns on. (g) The process of the LED turning on and off according to NIR heating and cooling under the (1,0) or (0,1) signal. This demonstrates that the logic gate can reconfigure between AND and OR functions depending on the presence of NIR illumination. Fig. 6. Process of synthesizing positively charged MXene (PMXene) by functionalizing the MXene surface with branched polyethyleneimide (BPEI). Fig. 7. Synthesis process of ES-PMXene and AT-NMXene. Fig. 8. XPS C 1s spectra of (a) pure MXene (NMXene), (b) MXene functionalized with a carboxylic acid, and (c) MXene functionalized with a branched polyethyleneimide (PMXene). In the case of PMXene, the -CONH and CN peaks observed at ~287.56 eV and ~286.08 eV indicate that the synthesis of PMXene was successful. Fig. 9. TEM and EDS elemental mapping images of NMXene and PMXene. The images show the elemental mapping of C (magenta), Ti (blue), O (green), F (yellow), and N (orange). (a) The EDS image of NMXene shows the presence of Ti, C, and functionalized functional groups (O, F). (b) In the case of PMXene, N atoms are additionally detected as the functional groups of NMXene are replaced by BPEI. Fig. 10. Thermogravimetric analysis (TGA) results of AT, AT-NMXene, ES, and ES-PMXene, with a heating rate of 10 degrees per minute. Fig. 11. Attenuated Total Reflection Fourier Transform Infrared Spectra (ATR-FTIR) Spectra of AT, AT-NMXene (1 wt%), ES, and ES-PMXene (1 wt%). 1636 cm⁻¹ -1 , 1621 cm -1 and 1410 cm -1 The absorption bands correspond to the -C=C- symmetric stretching, -C=C- asymmetric stretching, and -C=CH2- torsional modes, respectively. 3300-3500 cm -1 Vibrational peaks of water molecules are observed in ES and ES-PMXene in the range. Characteristic absorption peaks of MXene are not detected in AT-NMXene and ES-PMXene because a small amount of MXene is mixed into the ionic elastomer. Fig. 12. (a) Nyquist plot of AT (AT-PMXene) mixed with AT and 1 wt% PMXene. (b) Nyquist plot of ES (ES-NMXene) mixed with ES and 1 wt% NMXene. Both samples show a slight increase in bulk resistance, which indicates that there are no additional dissociated mobile ions in the ionic elastomer. Fig. 13. XPS N 1s spectra of (a) AT, (b) AT-NMXene (1 wt%), (c) ES, and (d) ES-PMXene (1 wt%). The integrated area ratio of the N- peak originating from the TFSI- anion increased 1.51-fold when 1 wt% NMXene was mixed into AT. When PMXene was mixed into ES, the integrated area ratio of the N+ peak originating from the EMIM+ cation increased 1.23-fold. These results indicate that the effective mobile ion was improved when NMXene and PMXene were added to AT and ES, respectively. Fig. 14. (a) Mobility [TFSI] in AT, AT-NMXene and AT-PMXene -Self-diffusion coefficient of anions. (b) Mobility in ES, ES-PMXene, and ES-NMXene [EMIM] + Cation self-diffusion coefficient. When 1 wt% NMXene is mixed with AT, [TFSI] - The self-diffusion coefficient of increased by approximately 29.70%. Similarly, when 1 wt% PMXene was mixed with ES, [EMIM] + The self-diffusion coefficient of increased by 61.87%. Fig. 15. (a) AT / AT, AT-NMXene / AT-NMXene (1 wt%). (b) Capacitance-frequency relationship of ES / ES and ES-PMXene / ES-PMXene (1 wt%). Electric double layer (EDL) capacitance increases in the lower frequency region (< 100 Hz). Fig. 16. (a) Real impedance-frequency curve at an ES-PMXene / AT-NMXene heterojunction. (b) Imaginary impedance-frequency curve at a homojunction. Fig. 17. (a) Current density of AT-NMXene / AT-NMXene (b) ES-PMXene / ES-PMXene homojunctions under various voltages. Fig. 18. Built-in potential of AT-NMXene / ES-PMXene heterojunction according to surface charge MXene content. A detailed analysis of these results is described in Supplementary Note 3. Fig. 19. (a) Schematic illustration of a strained ES-PMXene / AT-NMXene junction. (b) Nyquist plot of the stretched ES-PMXene / AT-NMXene junction. Fig. 20. 400 mW / cm² 2 Temperature change of a pure ES / AT junction diode exposed to NIR light. The pure ES / AT junction shows almost no temperature change. Fig. 21. Temperature change of an ES-PMXene / AT-NMXene junction diode heated photothermally during 10 NIR light On / Off cycles. Fig. 22. Temperature-dependent Nyquist plot of an ES-PMXene / AT-NMXene junction diode. As temperature increases, bulk resistance decreases, which is due to the ionic conductivity enhanced by the heat of the diode. Fig. 23. Behavior of charge relaxation frequency with temperature change. Bode impedance plots show the real impedance (Z') and imaginary impedance (Z'') at various temperatures. The two impedances (Z' and Z'') are identical at the charge relaxation frequency (τ-1), which is indicated by black and purple dots. (a) Bode plots of ES / AT and ES-PMXene / AT-NMXene (1 wt%) measured at room temperature (23 °C), (b) 30 °C, (c) 40 °C, (d) 50 °C, (e) 60 °C, and (f) 70 °C. (g) The charge relaxation frequency (τ-1) increases with increasing temperature. Therefore, (h) the charge relaxation time (τ) becomes shorter as the temperature increases. Fig. 24. Capacitance-frequency curves of ES / AT and ES-PMXene / AT-NMXene (1 wt%) at (a) room temperature (23°C), (b) 30°C, (c) 40°C, (d) 50°C, (e) 60°C, and (f) 70°C. (g) As temperature increases, capacitance increases, which indicates an improvement in electric double layer capacitance. Fig. 25. Ideal rectification ratio of (Cfor-Ceq) / (Ceq-Crev). Here, Cfor represents the capacitance at forward bias (+0.4 V), Ceq represents the capacitance at no bias, and Crev represents the capacitance at reverse bias (-0.4 V). As the temperature increases, the ideal rectification ratio increases. Fig. 26. Photograph of a reconfigurable logic gate using a stencil-printed liquid metal electrode circuit. FIG. 27. Square wave voltage signals set to frequencies fA (0.025 Hz) and fB (0.05 Hz) for inputs A and B, respectively. Fig. 28. Change in output current of a logic gate (ES-PMXene / AT-NMXene junction). As NIR light exposure increases at four logic input stages (1,1), (1,0), (0,1), and (0,0), the output current increases more rapidly. FIG. 29. (a) Output voltage of a reconfigurable logic gate corresponding to an AND gate. (b) Output voltage of a logic gate converted to an OR gate due to NIR exposure. (c) Output voltage converted back to an AND gate when NIR is turned off. Fig. 30. Circuit simulation of a reconfigurable logic gate using LT-SPICE and Falstad simulation programs. (a) An ion diode was modeled using LT-SPICE. When exposed to near-infrared (NIR) light, the resistance of the diode decreases, and consequently, the current increases. It shows that when NIR is applied and the resistance of the diode decreases, the threshold can be exceeded even if there is a signal in only one of the inputs. This exhibits behavior similar to that of the logic device of the present invention. (b) Simulation results using Falstad confirmed that when NIR is applied, the LED can be turned on even if there is a signal in only one of the inputs. Specific details for implementing the invention
[0028] Hereinafter, embodiments of the present invention will be described in detail with reference to the attached drawings. Since the present invention is susceptible to various modifications and may take various forms, specific embodiments are illustrated in the drawings and described in detail in the text. However, this is not intended to limit the present invention to the specific disclosed forms, and it should be understood that it includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the present invention. Similar reference numerals have been used for similar components in the description of each drawing. In the attached drawings, the dimensions of the structures are shown enlarged compared to the actual dimensions for the clarity of the present invention.
[0029] The terms used in this application are used merely to describe specific embodiments and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise. In this application, terms such as “comprising” or “having” are intended to specify the presence of the features, numbers, steps, actions, components, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, or combinations thereof. In the context of this specification, terms such as “about” may mean about ± 1%, about ± 2%, about ± 3%, about ± 4%, about ± 5%, about ± 6%, about ± 7%, about ± 8%, about ± 9%, or about ± 10% of the figures described in the specification.
[0030] In addition, the description of one aspect of the present invention may be applied identically or similarly to the description of other aspects for identical or similar configurations or terms.
[0031] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.
[0032] A composite ion-elastomer material with improved ion mobility according to an embodiment of the present invention may include an ion-elastomer; and a positively or negatively charged MXene contained within the ion-elastomer that interacts with one of a cation or anion.
[0033] In the context of this specification, the literal meaning of ion mobility refers to the ability of ions to move within a material. This is closely related to ion conductivity and influences not only electrical properties but also the chemical and physical properties of the material. Materials with high ion mobility can rapidly transmit electrical signals, thereby improving the performance of electronic devices. This characteristic can be particularly useful in applications requiring high-speed processing or rapid response, and can contribute to increasing the efficiency of electronic devices and sensors.
[0034] In the context of this specification, the literal meaning of ionoelastomer refers to a composite material in which an ionic substance is dispersed within a polymer matrix. Such materials possess both ion conductivity and elasticity and can be applied to various electronic devices. Ionoelastomers can play an important role, particularly in wearable devices or flexible electronic devices that require deformation. Furthermore, because they are solvent-free, they offer high environmental stability, making them suitable for long-term use and capable of maintaining stable performance under various environmental conditions.
[0035] The role of the aforementioned ion elastomer is to regulate electrical properties by including both immobilized and mobile ions. This enables the transmission and conversion of electrical signals and can improve the operating principles of electronic devices. In particular, ion conductivity can be enhanced by increasing the number of mobile ions through interaction with immobilized ions. This can help improve the response speed and efficiency of electronic devices and enable high performance in various electronic equipment. Ion elastomers also provide mechanical flexibility, allowing them to be processed into various shapes.
[0036] The role of the aforementioned MXene is to interact with ions within the ion elastomer to influence ion mobility. Positively charged MXenes can interact with anions, while negatively charged MXenes can interact with cations. This can improve conductivity and enhance electrical properties. Furthermore, since MXenes possess photothermal properties, they offer the possibility of controlling material properties using an external light source. This can contribute to increasing the flexibility and functionality of materials in various application fields.
[0037] The interaction between the MXene and the ion may involve bonding through attractive forces. As a result, ions capable of interacting with the MXene within the ion elastomer are relatively immobilized to form a dipole, thereby enhancing the mobility of ions that are not relatively immobilized. In one embodiment, the mobility of ions having the same charge as the MXene within the ion elastomer may be enhanced. Such an interaction can be particularly advantageous in electronic devices requiring high-frequency response and can contribute to optimizing performance in applications such as high-speed signal processing.
[0038] In one embodiment, the ionic elastomer may comprise one or more materials selected from the group comprising 1-ethyl-3-methylimidazolium (3-sulfopropyl) acrylate ([EMIM][SPA]) and 1-[2-acrylooxyethyl]-3-butylimidazolium bis(trifluoromethane)sulfonamide ([AEBI][TFSI]). However, the material of the ionic elastomer is not limited to the non-limiting examples described above. In one embodiment, the MXene is Ti3C2T x , and Ti3C2T with surfaces treated with polyethyleneimine (PEI) x It may include one or more materials selected from the group including. However, the material of the MXene is not limited to the non-limiting examples described above.
[0039] Meanwhile, an ion elastomer-based diode device with improved ion mobility according to an embodiment of the present invention may include an n-side comprising an ion elastomer; and a negatively charged MXene interacting with a cation contained within the ion elastomer; and an ion elastomer; and a positively charged MXene interacting with an anion contained within the ion elastomer; and a p-side in contact with the n-side.
[0040] In the context of this specification, the dictionary definition of a diode refers to an electronic device designed to allow current to flow in only one direction. Generally, it has a structure in which a p-type semiconductor or semiconductor-like material is joined with an n-type semiconductor or semiconductor-like material; when current flows in the forward direction, the resistance is low so that it flows easily, but when it flows in the reverse direction, the resistance is high so that it does not flow. These characteristics play an important role in the rectification of electrical signals or in logic circuits. In the present invention, the diode is based on an ion conductor and serves to control ion movement.
[0041] The roles of the n-side and the p-side are to transport ions carrying negative and positive charges, respectively, and thereby realize the rectification characteristics of the diode. The n-side contains ions carrying negative charges, and the p-side contains ions carrying positive charges, and the two sides are joined to control the flow of current.
[0042] In one embodiment, the diode element may further include a first electrode in contact with the n-side; and a second electrode spaced apart from the first electrode and in contact with the p-side. The role of the first electrode and the second electrode is to control the flow of current and to realize the electrical characteristics of the diode element. The first electrode is connected to the n-side and provides a charge transport path for negatively charged ions, and the second electrode is connected to the p-side and provides a charge transport path for positively charged ions. These electrodes play an important role in applying an electrical signal to the diode or transmitting an output signal to an external circuit.
[0043] In one embodiment, the ionic elastomer of the n-side may comprise one or more materials selected from the group including 1-[2-acrylooxyethyl]-3-butylimidazoliium bis(trifluoromethane)sulfonamide ([AEBI][TFSI]). However, the material of the ionic elastomer of the n-side above is not limited to the non-limiting examples described above, and other possible examples of ionic elastomers include 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM][PF6]), 1-ethyl-3-methylimidazolium trifluoromethanesulfonate ([EMIM][OTf]), 1-propyl-3-methylimidazolium bis(trifluoromethane)sulfonamide ([PMIM][TFSI]), 1-hexyl-3-methylimidazolium hexafluorophosphate ([HMIM][PF6]), 1-octyl-3-methylimidazolium bis(trifluoromethane)sulfonamide ([OMIM][TFSI]), and 1-dodecyl-3-methylimidazolium bis(trifluoromethane)sulfonamide ([DMIM][TFSI]). 1-Benzyl-3-methylimidazoleum hexafluorophosphate ([BzMIM][PF6]), 1-Allyl-3-methylimidazoleum bis(trifluoromethane)sulfonamide ([AlMIM][TFSI]), 1-Ethoxy-3-methylimidazoleum bis(trifluoromethane)sulfonamide ([EtOMIM][TFSI]), 1-(2-methoxyethyl)-3-methylimidazoleum bis(trifluoromethane)sulfonamide ([MeOEtMIM][TFSI]), 1-[(2-hydroxyethyl)-3-methylimidazoleum bis(trifluoromethane)sulfonamide ([HEMIM][TFSI]), 1-Butyl-1-methylpiperidinium bis(trifluoromethane)sulfonamide ([BMP][TFSI]), 1-hexyl-1-methylpiperidinium bis(trifluoromethane)sulfonamide ([HMP][TFSI]), 1-butyl-1-methylpyrrolidinium bis(trifluoromethane)sulfonamide ([BMPy][TFSI]), 1-hexyl-1-methylpyrrolidinium bis(trifluoromethane)sulfonamide ([HMPy][TFSI]), 1-ethyl-3-methylpyrrolidinium bis(trifluoromethane)sulfonamide ([EMPy][TFSI]),Examples include 1-propyl-3-methylpyrrolidinium bis(trifluoromethane)sulfonamide ([PMPy][TFSI]), 1-ethyl-3-methylpiperidinium bis(trifluoromethane)sulfonamide ([EMP][TFSI]), 1-propyl-3-methylpiperidinium bis(trifluoromethane)sulfonamide ([PMP][TFSI]), and 1-butyl-3-methylquinolinium bis(trifluoromethane)sulfonamide ([BMQ][TFSI]).
[0044] In one embodiment, the ionic elastomer of the p-side may comprise one or more materials selected from the group including 1-ethyl-3-methylimidazolium (3-sulfopropyl) acrylate ([EMIM][SPA]). However, the material of the ionic elastomer of the p-side above is not limited to the non-limiting examples described above, and other possible examples of ionic elastomers include 1-ethyl-3-methylimidazolium ethyl sulfate ([EMIM][EtSO4]), 1-ethyl-3-methylimidazolium methanesulfonate ([EMIM][MeSO3]), 1-ethyl-3-methylimidazolium acetate ([EMIM][OAc]), 1-ethyl-3-methylimidazolium diethyl phosphate ([EMIM][DEP]), 1-ethyl-3-methylimidazolium trifluoroacetate ([EMIM][TFA]), 1-ethyl-3-methylimidazolium chloride ([EMIM][Cl]), and 1-ethyl-3-methylimidazolium bromide ([EMIM][Br]). 1-ethyl-3-methylimidazoleum iodide ([EMIM][I]), 1-ethyl-3-methylimidazoleum bis(trifluoromethane)sulfonamide ([EMIM][TFSI]), 1-ethyl-3-methylimidazoleum bis(octafluoropentyl)phosphate ([EMIM][FAP]), 1-ethyl-3-methylimidazoleum heptafluorobutyrate ([EMIM][HFB]), 1-ethyl-3-methylimidazoleum tetrafluoroborate ([EMIM][BF4]), 1-ethyl-3-methylimidazoleum difluorophosphate ([EMIM][DFP]), 1-ethyl-3-methylimidazoleum nitrate ([EMIM][NO3]), 1-ethyl-3-methylimidazoleum Examples include cyanobromide ([EMIM][CNBr]), 1-ethyl-3-methylimidazolium hydrogen sulfate ([EMIM][HSO4]), 1-ethyl-3-methylimidazolium bis(trifluoromethane)sulfonate ([EMIM][OTf]), 1-ethyl-3-methylimidazolium dicyanomidazolid ([EMIM][DCN]), 1-ethyl-3-methylimidazolium phosphate ([EMIM][PO4]), and 1-ethyl-3-methylimidazolium oxodifluoroborate ([EMIM][ODFB]).
[0045] In one embodiment, the MXene included in the n-side is Ti3C2T x It may include one or more materials selected from the group including. Such MXenes may be negatively charged MXenes. However, the materials of the negatively charged MXenes are not limited to the non-limiting examples described above, and other possible examples of negatively charged MXenes include Ti2C, Ti3CN, Nb2C, V2C, Mo2C, Cr2C, Zr2C, Hf2C, Ta2C, Sc2C, Y2C, W2C, Mn2C, Fe2C, Co2C, Ni2C, Cu2C, Zn2C, Ga2C, In2C, and materials derived therefrom.
[0046] In one embodiment, the MXene included in the p-side is Ti3C2T with a surface treated with polyethyleneimine (PEI). x It may include one or more materials selected from the group including. Such MXenes may be positively charged MXenes. However, the materials of the positively charged MXenes are not limited to the non-limiting examples described above, and other possible examples of positively charged MXenes include Ti2C, Ti3CN, Nb2C, V2C, Mo2C, Cr2C, Zr2C, Hf2C, Ta2C, Sc2C, Y2C, W2C, Mn2C, Fe2C, Co2C, Ni2C, Cu2C, Zn2C, Ga2C, In2C, and materials derived therefrom, with their surfaces treated with PEI.
[0047] In one embodiment, the MXene included in the n-side or the p-side may be included in an amount of about 0.5 to 3 wt%. Although the scope of the present invention is not limited to the MXene content described above, ionic conductivity and physical properties can be optimized at the MXene content described above when referring to the embodiments to be described below. For example, if the MXene content is about 0.5 wt% or less, effective dispersion of the MXene is difficult, so the improvement in conductivity may be negligible, and if it exceeds 3 wt%, the mechanical flexibility of the ion elastomer may decrease. Therefore, a MXene content of about 0.5 to 3 wt% can help balance ionic conductivity and physical properties. Within this content range, the composite material maintains sufficient flexibility along with excellent electrical performance, making it potentially effective for use in various applications.
[0048] Meanwhile, a gate whose characteristics are controlled by light according to an embodiment of the present invention may further include a diode element comprising: an n-side comprising an ion elastomer; and a negatively charged MXene interacting with a cation contained in the ion elastomer; and a p-side in contact with the n-side, comprising an ion elastomer; and two or more input electrodes in contact with one of the n-side or the p-side; and an output electrode spaced apart from the input electrode and in contact with the other side.
[0049] The role of the input electrode and the output electrode is to handle the input and output of electrical signals, thereby enabling the diode device to perform the desired function. The input electrode receives an electrical signal from an external circuit and transmits it to the n-side or p-side of the diode device, inducing ion movement and causing current to flow. On the other hand, the output electrode serves to transmit the electrical signal generated by the diode device to the external circuit. Through the arrangement and interaction between these electrodes, the logic state of the gate can be controlled, and various logic operations can be performed by changing the characteristics of the diode through light irradiation. As a result, flexible and efficient control can be achieved in various electronic circuits, and significant advantages can be provided in applications requiring high-speed signal processing and accurate logic operations.
[0050] The meaning of the gate according to the embodiment of the present invention being characterized by light is that changes are applied to the physical or chemical properties of the gate depending on the presence or absence of light irradiation and the amount of light irradiation. For example, when light is irradiated, the resistance of the diode device according to the embodiment of the present invention may be lowered. This may be a result of the temperature rising upon light irradiation due to the photothermal effect of MXene, and such a temperature rise can improve conductivity by increasing the mobility of ions. As a result, the diode device can exceed the threshold voltage even with a smaller or weaker input signal upon light irradiation, thereby enabling the transition from an AND GATE mode to an OR GATE mode. This characteristic can be usefully applied in various optical-based electronic devices and can provide an innovative solution for high-speed signal processing and precise control.
[0051] In one embodiment, the diode device may include an ion elastomer-based diode device with enhanced ion mobility according to the embodiment of the present invention described above. Such a diode device includes a negatively charged MXene and a positively charged MXene on the n-side and p-side, respectively, thereby improving electrical characteristics. The combination of the ion elastomer and the MXene significantly increases ion mobility, which can contribute to optimizing the electrical performance of the diode device.
[0052] In particular, as the resistance decreases with light irradiation, the gate can perform both AND and OR gate functions. For example, when no light is irradiated or the irradiation amount is low, the resistance is high, so it can operate as an AND gate where signals must be applied to two or more input electrodes to exceed the threshold voltage. Conversely, when the irradiation amount is high, the resistance decreases, allowing the threshold voltage to be easily exceeded even with a signal applied to only one input electrode, enabling it to operate as an OR gate. This allows for the flexible switching of the diode device's operating mode by adjusting the intensity of the light source, which can assist in performing more complex operations in various logic circuits. This functionality offers the potential to enhance efficiency in high-performance computing systems and smart electronic devices, and to significantly increase the freedom of circuit design. Furthermore, by possessing the ability to respond in real-time to environmental changes or external signals, it can make a significant contribution to the development of adaptive electronic systems.
[0053] Meanwhile, a light control device according to an embodiment of the present invention may include a gate whose characteristics are controlled by light; and a light source capable of irradiating light onto the gate. In one embodiment, the gate may include a gate according to the embodiment of the present invention described above. Accordingly, the electrical characteristics and performance of the gate can be dynamically controlled according to the irradiation conditions of the light source. This provides the possibility to optimize the operation of an electronic device in real time through external control using light. This function can play an important role in the development of high-performance smart electronic systems by increasing energy efficiency in various electronic devices and enabling rapid adaptation to environmental changes. Furthermore, such a light control device can contribute to flexible and adaptable electronic circuit design in wearable devices or Internet of Things (IoT) devices.
[0054] The role of the light source is to irradiate the gate with light to alter the characteristics of the diode device. Specifically, the light source emits light of a specific wavelength to induce the photothermal effect of the MXene, thereby raising the temperature of the ion elastomer. This temperature increase enhances ion mobility, which can regulate the flow of current. By adjusting the irradiation conditions of the light source, the electrical characteristics of the gate can be finely controlled, which helps to achieve optimal performance in various environments. Therefore, the light source plays a crucial role in controlling the operation of electronic devices in real time and enabling various operating modes depending on the application. This allows for high efficiency and adaptability in smart electronic systems and various high-performance electronic devices.
[0055] This device is made of a flexible, stretchable, and harmless material, and can be used in smartwatches, smart clothing, assistive devices, etc., to serve as a human-interactive device. In the case of previously reported tunable logic gates, not only are toxic materials such as perovskite used, but they also lack flexible or stretchable properties, making them unsuitable for use as human-interactive devices.
[0056] Furthermore, since portability is critical for such human-interactive devices, miniaturization and circuit simplification are required. The device proposed in this invention can perform the functions of both an AND gate and an OR gate by controlling near-infrared (NIR) light with a single component. This offers the advantage of significantly simplifying the circuit, unlike conventional circuit technologies that control AND and OR gates using complex structures. It is expected that utilizing the technology proposed in this invention will enable the creation of tunable logic gates capable of future miniaturization and circuit simplification.
[0057] The embodiments of the present invention are described below. However, the embodiments described below are merely partial embodiments of the present invention, and the scope of the present invention is not limited to the following embodiments.
[0058] [[result]]
[0059] [Synthesis and Characterization of AT-NMXene and ES-PMXene]
[0060] Figure 1a shows n-type and p-type ionic elastomers containing mobile anions and cations, respectively. 1-[2-acryloyloxyethyl]-3-butylimidazolium bis(trifluoromethane)sulfonimide ([AEBI][TFSI], denoted as AT) was selected as the n-type ionic elastomer, where the [TFSI] anion is mobile and the [AEBI] cation is immobilized to the polymer main chain. Similarly, 1-ethyl-3-methylimidazolium (3-sulfopropyl) acrylate ([EMIM][SPA], denoted as ES) was selected as the p-type ionic elastomer, where the [EMIM] cation is mobile and the [SPA] anion is immobilized to the polymer main chain. Traditional Ti3C2T with abundant functional groups (=O, -OH, -F) and a negative surface dipole. x The surface of the MXene nanosheet is negatively charged (schematically shown in Fig. 1a), and this is denoted as NMXene. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) confirmed the two-dimensional structure of the NMXene nanosheet, and the results are shown in Fig. 1b(i) and Fig. 1b(ii), respectively.
[0061] To fabricate MXene nanosheets (denoted as PMXene) having a positively charged surface potential, the existing functional groups (-OH) of NMXene were replaced with carboxyl groups (-COOH) and subsequently mixed with branched poly(ethyleneimide) (BPEI) (Fig. 1a). A condensation reaction between BPEI and the carboxyl groups occurred in NMXene, causing the amine groups of PEI to positively charge the MXene surface (as shown in Fig. 1a). The detailed synthesis procedures for NMXene and PMXene are described in Figs. 6 and 7. The two-dimensional structure of PMXene was also confirmed via SEM and TEM, and the results are shown in Figs. 1b(iii) and 1b(iv), respectively.
[0062] The synthesis of PMXene nanosheets was confirmed via Fourier Transform Infrared Spectroscopy (FT-IR), and the results are shown in Fig. 1c. For PMXene, 3430 cm⁻¹ -1 , 1625 cm -1 , 1392 cm -1 , 1296 cm -1 , 1108 cm -1 Characteristic absorption peaks were observed, corresponding to the stretching vibrations of -OH, C=O / NH, OH, CN, and CF bonds. The successful synthesis of PMXene nanosheets was further verified through X-ray photoelectron spectroscopy (XPS) analysis, and the results are shown in Fig. 8. In the C1s spectrum of PMXene, intense peaks appeared at approximately 287.6 eV and 286.1 eV, corresponding to the -CONH and CH peaks. Additionally, the formation of PMXene and NMXene was confirmed via energy-dispersive X-ray spectroscopy (EDX). For NMXene, characteristic X-ray spectra corresponding to O, OH, and F were observed, while for PMXene, additional X-ray emissions originating from N were detected due to the PMXene being modified with BPEI (Fig. 9). The surface charges of NMXene and PMXene were confirmed by zeta potential measurements, with NMXene showing a potential value of -34 mV and PMXene showing +40 mV (see Fig. 1d).
[0063] The two MXenes were further investigated using high-resolution X-ray diffraction analysis (HR-XRD), and the results are shown in Fig. 1e. Strong (002) reflections were observed at 6.98° and 6.34° in the X-ray diffraction (XRD) patterns of NMXene and PMXene, respectively. The reason for the increased (002) spacing in PMXene appears to be that NMXene was intercalated with a long and flexible BPEI.
[0064] NMXene and PMXene were mixed with AT and ES, respectively, to form two ionoelastomeric complexes named AT-NMXene and ES-PMXene, photographs of which are shown in Fig. 1f. According to the XRD results presented in Fig. 1g, the (002) reflection of NMXene and PMXene was maintained in AT-NMXene and ES-PMXene. Reflections at approximately 19.1° and 23.3° correspond to the (120) and (032) reflections of the PEGDA crystals. In the case of AT and AT-NMXene, almost no reflection of PEGDA was observed, which is because the crystallinity was significantly reduced due to ion-dipole interactions between the polycation and oxygen.
[0065] The thermal properties of AT-NMXene and ES-PMXene were investigated via differential scanning calorimetry (DSC), and the results are shown in Fig. 1h. The melting temperatures of PEGDA crystals in ES and ES-PMXene were found to be approximately 50.73 °C and 50.75 °C, respectively. As expected, no melting peaks were observed in AT and AT-NMXene. Additionally, according to thermogravimetric analysis (TGA) results, ES and ES-PMXene contained approximately 2.677% residual moisture due to their hygroscopic properties. Meanwhile, almost no water was detected in AT and AT-NMXene due to the characteristics of the fluorinated TFSI anion (see Figs. 10 and 11).
[0066] The mechanical properties of AT-NMXene and ES-PMXene were investigated through tensile stress-strain experiments, and the results are shown in Fig. 1i. When MXene was mixed with ionoelastomer, the elongation decreased, while the modulus of the sample increased slightly due to the high modulus characteristics of the MXene nanosheets. The maximum tensile strain of AT-NMXene and ES-PMXene containing 1 wt% NMXene and 1 wt% PMXene was found to be approximately 450%.
[0067] [Ionic Properties of AT-NMXene and ES-PMXene]
[0068] The ionic conductivity of AT-NMXene and ES-PMXene was determined by AC impedance measurements, and the results are shown in Figures 2a and 2b. A Nyquist plot was used to measure the bulk resistance (RB) of the samples, and the ionic conductivity (σ) was calculated using the following equation based on the measured bulk resistance:
[0069]
[0070] Here, ρ is resistivity, l is the sample thickness (l = 500 μm), and A is the area (A = 0.25 cm²) 2 The RB of AT-NMXene and ES-PMXene decreased as the amounts of NMXene and PMXene, respectively, increased, and consequently, the ionic conductivity of both samples increased proportionally to the MXene content. As shown in Fig. 2a, when 3 wt% NMXene was added to AT, the RB decreased from 0.107 MΩ in the absence of NMXene to approximately 0.049 MΩ. Similarly, according to Fig. 2b, the RB of ES-PMXene decreased from 1.005 MΩ in the absence of PMXene to approximately 0.447 MΩ when 3 wt% PMXene was added. It should be noted that when NMXene was mixed with ES or PMXene was mixed with AT, the bulk resistance values of the two samples hardly changed. This implies that there is no continuity of the MXene nanosheets added due to the low content (1 wt%) of the conductive MXene component (Fig. 12). These results indicate that the resistance of AT-NMXene and ES-PMXene is reduced as additional mobile ions are generated due to specific interactions between AT and NMXene and ES and PMXene.
[0071] The enhancement of the ionic conductivity of AT-NMXene and ES-PMXene due to additional mobile ions in the two samples is confirmed by the N1s XPS experimental results, which are shown in Figs. 2c and 2d, respectively (Fig. 13 and Supplementary Note 1). TFSI in the XPS spectrum - The N-peak integrated area ratio of EMIM+ increased 1.51-fold when 1 wt% NMXene was mixed with AT. Meanwhile, the N+ peak integrated area ratio of EMIM+ increased 1.23-fold when 1 wt% PMXene was mixed with ES. Since XPS peak areas are proportional to the concentration of the corresponding element, these results suggest that the concentration of effective mobile ions increased in both samples. Based on the XPS results, it is presumed that the cationic polymer backbone preferentially binds to NMXene, which has a negatively charged surface, allowing mobile anions to be easily released from the backbone. The release of mobile anions effectively improved the ionic conductivity of the samples. In the case of AT-NMXene, the polymer backbone with immobilized cations interacted with NMXene to release mobile anions into the system and improve the ionic conductivity of the samples. Similarly, in the case of ES-PMXene, the polymer backbone with immobilized anions interacted with PMXene, increasing ionic conductivity.
[0072] The interactions between AT and NMXene, and between ES and PMXene, were further verified through diffusion difference spectroscopy (DOSY) measurements, and the results are shown in Figs. 2e and 2f, respectively. Mobility [TFSI] in AT and ES - (D[TFSI] - The self-diffusion coefficients of ) and [EMIM]+(D[EMIM]+) were calculated using the Stejskal-Tanner equation. The detailed method for this analysis is presented in Supplementary Note 2. D[TFSI] of AT-NMXene - The value is 2.495 X 10 when 1 wt% NMXene is mixed with AT. -11From 3.236 X 10 -11 It increased, showing an increase in the diffusion coefficient of approximately 29.70%. Similarly, the D[EMIM]+ value in ES-PMXene was 4.207 × 10 when 1 wt% PMXene was mixed with ES. -11 From 6.810 X 10 -11 It increased to show a 61.87% increase in the diffusion coefficient. These results indicate that adding NMXene and PMXene to AT and ES, respectively, [TFSI] - This indicates that the mobility of [EMIM]+ is enhanced, which is consistent with the ionic conductivity (Figs. 2a and 2b). Notably, when PMXene and NMXene were added to AT and ES, respectively, D[TFSI] - It is that D[EMIM]+ has hardly changed (Fig. 14). The improvement in ionic conductivity of AT-NMXene and ES-PMXene is a result of increased concentration and mobility of free-moving ions due to ion-dipole interactions between the immobilized cation (AT) and NMXene and between the immobilized anion (ES) and PMXene, which is conceptually illustrated in the schematics of Figs. 2g and 2h, respectively. In addition, it can be confirmed in Fig. 15 that the increase in the concentration of mobile ions improves the electric double layer (EDL) capacity of AT-NMXene and ES-PMXene.
[0073] [Ionic Performance of Heterojunction ES-PMXene / AT-NMXene Diodes]
[0074] When ES-PMXene and AT-NMXene are physically stacked, a junction diode is formed along with upper and lower electrodes, as schematically shown in Fig. 3a. At the interface of the ES-PMXene / AT-NMXene junction, the [EMIM] of ES-PMXene + Cations diffuse into AT-NMXene, and [TFSI] of AT-NMXene -Anions diffuse into the ES-PMXene. This diffusion is an entropy-driven process, resulting in only cross-linked [SPA]- anions remaining in the ES-PMXene and only [AEBI]+ cations remaining in the AT-NMXene. Additionally, long-range transport of [SPA]- anions and [AEBI]+ cations is restricted at the junction. Under these conditions, a typical ion double layer (IDL) is formed, which is similar to the depletion layer of an electronic pn semiconductor junction (see Fig. 3b). Due to the IDL, an interfacial electric field is formed from the ES-PMXene to the AT-NMXene, which generates drift currents for mobile ions. This is similar to the classical pn semiconductor model.
[0075] When a forward voltage is applied to an ES-PMXene / AT-NMXene junction diode, mobile ions ([EMIM] within the ES-PMXene + ) moves to the AT-NMXene interface, and mobile ions ([TFSI] within the AT-NMXene - ) migrate to the ES-PMXene interface. Consequently, the IDL at the junction interface is destroyed, allowing current flow through the junction. Conversely, when a reverse voltage is applied, cations within the ES-PMXene move away from the junction interface toward the electrode, while anions within the AT-NMXene move away from the junction. This phenomenon reconstructs the IDL at the junction interface. In this case, current flow is significantly restricted, and the diode behaves similarly to a capacitor.
[0076] The impedance characteristics of the ES-PMXene / AT-NMXene heterojunction under forward and reverse bias were investigated under DC bias using an electrochemical impedance spectrometer (EIS), and the results are shown in Figures 3c and 3d. The Nyquist plot in Figure 3c was obtained as a function of forward and reverse bias by measuring the real impedance (Z') and imaginary impedance (Z") values in the frequency range between 100 m Hz and 1 MHz. The total impedance consists of the real impedance generated by the resistors and the imaginary impedance generated by the capacitors and inductances (Z = Z' + Z"). In the low-frequency region (below 100 Hz), the total impedance decreased as the imaginary impedance was significantly reduced by forward bias. However, as shown in Figure 3c, the total impedance remained almost unchanged under reverse bias. These results indicate that the interfacial resistance of the ES-PMXene / AT-NMXene junction decreases with forward bias, thereby promoting the transport of mobile ions to the junction interface.
[0077] Additionally, Fig. 3d shows a Bode plot representing the relationship between frequency and phase angle as a function of forward and reverse bias of the ES-PMXene / AT-NMXene heterojunction. The phase angle represents the angle between the real and imaginary components of the impedance vector. In the low-frequency region (below 100 Hz), the reduction in imaginary impedance due to forward bias resulted in a decrease in the phase angle associated with the decay of the IDL. The current density of the ES-PMXene / AT-NMXene (1 wt%) heterojunction increased significantly under forward bias, while it decreased significantly under reverse bias, exhibiting characteristic ion rectifier diode characteristics as shown in Fig. 3e.
[0078] The results of investigating the ionic characteristics of the ES-PMXene / AT-NMXene heterojunction according to the addition amounts of PMXene and NMXene are shown in Figs. 3f, 3g, and 3h. As can be seen in the Nyquist plot (Fig. 3f), the bulk resistance of the junction diode decreased from 0.499 MΩ (0 wt%) to 0.305 MΩ (0.5 wt%), 0.204 MΩ (1 wt%), and 0.020 MΩ (3 wt%).
[0079] The Bode impedance plot (Fig. 3g) shows that the impedance of the heterojunction decreased with the addition of MXene in the low-frequency region (below 100 Hz). This is due to the improved ion mobility associated with the conductive MXene. Increased current density in the heterojunction diode containing MXene was distinctly observed, particularly under forward bias. Changes in capacitance with frequency also demonstrated that a higher MXene content enables a response even at higher frequencies (Fig. 3h).
[0080] With the inclusion of MXene, the current density of the heterojunction diode increased, and a significant increase was observed under forward bias (Fig. 3i). Charge density can be calculated by integrating the current density over time, and the difference in charge density between forward and reverse bias (Qf / Qr) showed that the rectification ratio increased with increasing MXene content (Fig. 3j). Furthermore, as the MXene content increased, the charge density in the forward direction increased with a larger range of variation than the charge density in the reverse bias (Fig. 3j).
[0081] [NIR control of ES-PMXene / AT-NMXene diodes]
[0082] When the ES-PMXene / AT-NMXene junction diode was exposed to NIR (945 nm wavelength), an increase in the diode's temperature was observed due to the NIR photothermal effect of MXene. This is illustrated in Fig. 4a. The temperature change of the diode according to the NIR exposure time was monitored using a forward infrared (FLIR) camera. An ES-PMXene / AT-NMXene diode containing 1 wt% MXene was exposed to NIR (400 mW / cm²). 2 When exposed to ), the temperature of the diode started at room temperature (24 ℃) and rose to 30, 40, 50, and 60 ℃ after 0.5, 6, 24, and 54 seconds, respectively. After 100 seconds, it reached approximately 73.5 ℃, which is shown in the sequence of images in Fig. 4a. The photothermal effect of the diode originating from MXene was confirmed through UV-Vis-NIR spectroscopy, and it was found that the composite containing PMXene or NMXene absorbed more light over a wider wavelength range, particularly in the NIR region, than the ionic elastomer without MXene (Fig. 4b).
[0083] The results of investigating the temperature change according to NIR power of an ES-PMXene / AT-NMXene junction diode containing 1 wt% MXene are shown in Fig. 4c. As expected, after exposure to NIR for 400 seconds, the saturation temperature of the device was at NIR powers of 100, 200, 300, and 400 mW / cm² 2 At , the values increased to approximately 44.3, 50.7, 62.3, and 73.5 °C, respectively. In addition, the photothermal heating rate, defined by the slope (K min⁻¹) obtained by fitting the temperature change curve during 1 minute of NIR exposure, was calculated as a function of NIR power. 100, 200, 300, 400 mW / cm² 2 9.84, 16.22, 22.07, and 30.28 K min at NIR power, respectively -1A heating rate was achieved. In contrast, the pure ES / AT showed almost no change upon NIR exposure (Fig. 20). When the NIR light was turned off, the temperature of the diode decreased rapidly, as shown in Fig. 4d. Reversible heating and cooling of the 1 wt% heterojunction diode through the ON / OFF switching of NIR was confirmed through a NIR repeated exposure cycle test (Fig. 4d), and consistent heating and cooling occurred during 10 cycles (Fig. 21).
[0084] The ionic characteristics of the ES-PMXene / AT-NMXene junction diode containing 1 wt% MXene were also investigated as a function of NIR exposure, and the Nyquist plots of the diode exposed to NIR at various powers are shown in Fig. 4e. The bulk resistance of the diode decreased with increasing NIR power due to ionic conductivity enhanced by heat. NIR power at 0, 100, 200, 300, and 400 mW / cm² 2 At this point, the bulk resistance decreased to 238.4, 36.2, 8.2, 5.4, and 2.3 kΩ, respectively. The change in the diode's bulk resistance observed during NIR exposure was identical to the change in resistance observed at the corresponding temperature obtained due to NIR exposure, confirming the photothermal effect originating from the MXene within the diode (Fig. 22). The rectification ratio of the ES-PMXene / AT-NMXene junction diode increased with NIR exposure, as shown in Fig. 4f. The relative rectification ratio, calculated by dividing the rectification ratio without NIR irradiation, increased to 2.113 when 1 wt% MXene was mixed. Upon NIR exposure, the relative rectification ratio was 100, 200, 300, and 400 mW / cm² 2 At the NIR power, it further increased to 2.45, 2.67, 3.11, and 3.13, respectively. As expected, in the diode without MXene, the rectification ratio hardly changed with NIR exposure (Fig. 4f).
[0085] Furthermore, Fig. 4g is 400 mW / cm² 2 The charge density plots as a function of the forward and reverse voltages of the diode during NIR exposure are shown, exhibiting distinct rectification characteristics compared to the diode without NIR exposure, supporting the improved rectification ratio of the device during NIR exposure. The rectification performance observed in ion diodes during near-infrared (NIR) irradiation improves with increasing temperature, which is attributed to an increase in ionic conductivity. Increased ionic conductivity reduces the charge relaxation time (τ = ε / σ = RC), accelerating the response speed and enabling faster charge transfer, particularly under high-frequency conditions (Fig. 23). Furthermore, at high temperatures, ion dissociation is further promoted, increasing the effective number of mobile ions. This increases the electric double layer (EDL) capacitance and contributes to an increase in current under forward bias. The results of a systematic study on the increase in EDL capacitance and the ideal rectification ratio of the ion diode with increasing temperature are presented in Figs. 24 and 25. A detailed analysis of this is included in Supplementary Note 5. By facilitating reversible temperature control of a heterojunction diode using the NIR photothermal effect and thereby enabling control of the device's current density, a new NIR responsive reconfigurable ion logic gate could be developed as follows.
[0086] [NIR Reactive Reconfigurable Ion Logic Gate]
[0087] NIR-responsive reconfigurable ion logic gates were fabricated using an ES-PMXene / AT-NMXene (1 wt%) junction and a stencil-printed liquid metal eutectic gallium-indium (EGaIn) connector, and the results are shown in Fig. 5. An ion AND logic gate consists of two vertically stacked ion diodes and a resistor (RAT-MXene) formed by an EGaIn / ES-PMXene / AT-NMXene (1 wt%) heterojunction / EGaIn, and the connection method between them is schematically illustrated in Fig. 5a. In the fabricated ion AND logic gate, the ion diodes and resistors each have a 5 x 5 mm 2 and 1.5 x 1.5 mm 2 An EGaIn electrode of size was used, and the width of the EGaIn connector was set to 1 mm. The equivalent circuit of an ion logic gate with two inputs (A and B) and an output (C terminal) is shown in Fig. 5a and Fig. 26. This logic gate initially operates as an AND gate, but when exposed to NIR, it switches from an AND gate to an OR gate due to the photothermal effect, and returns to an AND gate when cooled. This is shown in Fig. 5b.
[0088] In an AND logic gate, output current flows only when the voltages of input terminals A and B are higher than the threshold input voltage. On the other hand, in an OR logic gate, output current flows when the voltage of A or B is higher than the threshold voltage. Square wave voltage signals programmed with frequencies fA (0.025 Hz) and fB (0.05 Hz) for inputs A and B, respectively, were used (Fig. 27). Four logic input states ((0,0), (0,1), (1,0), (1,1)) were set by combining inputs A and B, and experiments were conducted by varying the driving voltages of A and B.
[0089] First, an ion AND logic gate based on output current was developed. The output current values when voltage bias is applied to inputs A and B are shown in FIG. 5c. When the input signal is set to +1 V, it is defined as '1'. Four logic input states ((1,1), (1,0), (0,1), (0,0)) were set for inputs A and B. The measurement cycle was conducted for 40 seconds, and A and B were both kept in the ON state (1,1) for the first 10 seconds. Then, B was turned off and A was kept in the ON state (1,0) for 10 seconds. Next, A was turned off and B was kept in the ON state (0,1) for 10 seconds. Finally, the cycle was completed by keeping both A and B in the OFF state (0,0) for 10 seconds.
[0090] The output value was considered '1' when the output current from inputs A and B exceeded a threshold. The logical '1' state at output C was defined as when the output current exceeded an upper threshold of 0.6 μA, and the logical '0' state was defined as when the output current was 0.6 μA or less. When there was no input signal A or B, or when there was only one input, the output current did not reach the threshold, resulting in an output value of '0'. Therefore, the ion diode effectively operated as an AND gate (left side of Fig. 5c).
[0091] The output current of the logic gate was manipulated by the photothermal effect of the charged MXene, which is shown in the center of Fig. 5c. During the input cycle, the output current of the logic gate increased with increasing NIR output (exposure for 40 seconds) at all input stages except for the final state (both A and B off). The NIR output was 400 mW / cm² 2At this point, the output current of input A or B exceeded the threshold value (0.6 μA). In this case, the three stages (1,1), (1,0), and (0,1) became logical '1' states, while the (0,0) stage remained in a logical '0' state. Therefore, the logic gate operated as an OR gate. Additionally, the increase in output current varied depending on the NIR output and exposure time (Fig. 28). After cooling, the logic gate switched back to an AND gate, with only the (1,1) state maintaining a logical '1' state and the remaining three states transitioning to a logical '0' state (Fig. 5c right).
[0092] As shown in Fig. 5d, nine consecutive AND gates in the absence of NIR exposure and an OR gate appearing upon NIR exposure were verified over 10 programming cycles. The OR gate consistently appeared upon NIR exposure (the pink shaded cycle in Fig. 5d), and when the NIR was turned off and cooled to room temperature, it operated as an AND gate. The reconfigurable switching between AND and OR was performed repeatedly without performance degradation.
[0093] To enhance the reliability of the NIR reactive logic gate, a resistor was added to the output line to convert the current signal of the logic gate into a voltage and amplify it (Figs. 5e, 29). The converted and amplified output voltage was measured using a data acquisition system (DAQ) (Fig. 5f). It was confirmed that the logic gate operates as an AND gate even in voltage mode (Fig. 29a), and the NIR output was 400 mW / cm² 2 The performance of the OR gate was verified at this time (Fig. 29b). After cooling, the logic gate was restored to an AND gate (Fig. 29c). Similar to the current mode, 10 programming cycles were repeated, resulting in 9 AND gates and 1 OR gate (pink shaded area in Fig. 5e).
[0094] Finally, the transition between AND and OR gates was visually demonstrated using an Arduino and an LED (Fig. 5f). In the experiment, the LED was off in the AND state, and turned on when the OR gate state was reached via NIR exposure. The performance of the reconfigurable logic gate was verified through equivalent circuit simulation using LT-SPICE and Falstad programs (Fig. 30). The present invention simplifies circuit design by reducing the number of components and offers the potential for various low-power consumption and low-cost multi-functional logic applications.
[0095] [[argument]]
[0096] In the present invention, reconfigurable AND and OR logic gates based on NIR irradiation were implemented using a near-infrared (NIR) responsive ion junction. The ion junction diode was fabricated by vertically stacking p-type and n-type ion elastomers, each containing positively and negatively charged MXenes, between upper and lower liquid metal electrodes. The positive and negative surface potentials of PMXene and NMXene applied to the p-type and n-type ion elastomers, respectively, promoted ion-dipole interactions between the cross-linked p-type ion elastomer main chain and PMXene, and between the cross-linked n-type ion elastomer main chain and NMXene. As the dissociation of mobile ions in the ion elastomer was promoted, the current rectification performance of the diode was improved. More importantly, by utilizing the photothermal effect generated when PMXene and NMXene are irradiated with NIR, the current rectification performance of the diode is further increased when exposed to NIR. The diode developed in this invention can adjust current rectification performance according to NIR irradiation, and by utilizing this, a new reconfigurable logic gate capable of reliably reversibly switching an AND gate to an OR gate was implemented.
[0097] The present invention provides the following major achievements in the advancement of iontronics devices: (i) Enhanced stability: The device is implemented as a liquid-free ion-elastomer solid-state system, overcoming the limitations of existing hydrogel-based iontronic logic devices and significantly improving operational stability. (ii) Improved performance: It was demonstrated that the performance of iontronics materials can be fundamentally improved by utilizing nanomaterials with tuned surface potentials without relying on miniaturization, thereby suggesting the possibility of expanding the scope of organic-inorganic hybrid material design. (iii) First realization of a photothermal reconfigurable ion diode: While conventional ion diodes depended on changes in ion concentration, temperature, and pH, the present invention introduced a NIR-based non-contact reversible ion diode and logic gate by utilizing the high photothermal conversion efficiency of MXene. (iv) Expansion of Application Fields: Since NIR and temperature are biocompatible stimuli, the NIR-responsive ion diode proposed in this invention is highly promising for applications such as non-biological-biological interfaces, neuroprosthetics, and neuromorphic computing, and can further expand the scope of utilization for next-generation iontronics. In conclusion, this invention implements a reconfigurable logic gate based on an NIR-responsive solid-state ion junction diode and demonstrates the potential for success in multifunctional smart biomedical and sensing iontronics.
[0098] [[method]]
[0099] [ingredient]
[0100] 1-Ethyl-3-Methylimidazolinium Chloride ([EMIM]Cl, Sigma-Aldrich, 900771), Potassium 3-Sulfopropyl Acrylate (K[SPA], Sigma-Aldrich, 251631), Methoxyphenol (Sigma-Aldrich, 54050), 1-Butylimidazole (Sigma-Aldrich, 348414), Lithium Bis(Trifluoromethanesulfonylamide) Salt (Li[TFSI], Sigma-Aldrich, 544094), 2-Hydroxyethyl Acrylate (2-HEA, Sigma-Aldrich, 292818), 2,2'-AzobisIsobutyronitrile (AIBN, Dawon Science, A1482), Polyethylene Glycol (PEG, Sigma-Aldrich, 81260), Triethylamine (Sigma-Aldrich, 471283), acryloyl chloride (Sigma-Aldrich, 549797), potassium carbonate (K2CO3, Sigma-Aldrich, P5833), magnesium sulfate (MgSO4, Sigma-Aldrich, 746452), ethanol, acetonitrile, dichloromethane (DCM), and deionized water (DI water) were purchased from Sigma-Aldrich. Liquid metal (EGaIn, 75.5 wt% Ga, 24.5 wt% In, Sigma-Aldrich, 495425) and 2-bromoethyl acrylate (L12502-06) were purchased from Alfa Aesar. All remaining chemicals were purchased from Sigma-Aldrich and used as is. MXene suspension (10 mg mL) -1 ) was purchased from XinXi Technology Co., Ltd. located in Foshan, China. VHB 4905 and VHB 4910 were purchased from 3M and used as is.
[0101] [Preparation of NMXene and PMXene Powders]
[0102] To prepare PMXene powder, carboxyl-modified MXene was first synthesized according to the reported method. For this purpose, an MXene solution (1 mg mL)-1 300 mL of BPEI was mechanically stirred continuously for 40 minutes to maintain a well-dispersed state. Subsequently, 5 g of ClCH2COOH was gradually added to the mixed suspension while stirring. 32 mL of NaOH solution (6.25 mol / L) was added to remove residual chemical functional groups. The mixture was reacted at 60 °C for 3 hours to achieve a complete reaction. To increase purification efficiency, the mixture was washed with DI water and dialyzed several times. MXene-COOH modified with carboxyl groups was then synthesized. 2 mL of BPEI (86 mg mL) -1 ) in 40 mL of exfoliated MXene-COOH dispersion (0.4 mg mL -1 It was added to ). Subsequently, after stirring for 20 minutes, the mixture was stirred at 90 °C for 2 hours. The resulting stable black dispersion was centrifuged at 15,000 rpm and washed several times with DI to remove excess polymer. Finally, positively charged MXene functionalized with BPEI was obtained. PMXene powder was obtained via freeze-drying. The overall synthesis process is shown in Figures 6 and 7. Conventional Ti3C2T x MXene has functional groups such as -O, -OH, and -F, providing a negatively charged surface. Therefore, NMXene powder was obtained by freeze-drying conventional MXene.
[0103] [Preparation of ES-PMXene and AT-NMXene]
[0104] [EMIM][SPA] for ES and [AEBI][TFSI] for AT were synthesized following the reported procedure. PEGDA 6k was also synthesized according to the procedure reported in previous studies. ES and AT were mixed with PEGDA 6k, 2-HEA, and an initiator (AIBN), as reported in previous studies. Subsequently, the prepared MXene powder was uniformly dispersed in an ionic elastomer solution via sonication. The mixed solution was poured into a pre-fabricated VHB film mold. The mixture was heat-cured in a glove box at 60 °C for 2 hours. After the reaction, the product was washed with DCM to remove unreacted monomers and dried again at 60 °C for 2 hours (Fig. 7).
[0105] [Characteristic Analysis]
[0106] XRD measurements were performed using a SmartLab (Rigaku) diffuserometer with Cu Kα radiation to identify the crystallinity of ionic elastomers and MXene nanosheets in the 2θ range of 2–90°. Peak spectrum scans were performed using an ATR-FTIR spectrometer (Vertex 70, Bruker). The zeta potential of charged MXene was measured using a particle size and zeta potential analyzer (Otsuka Electronics, ELS-Z1000). Thermal analysis (TGA) of the ionic elastomers was performed using a thermogravimetric analyzer (TA Instruments Q500), with the temperature increasing from 25 °C to 700 °C at a rate of 10 °C / min and analyzed in an N2 atmosphere. DSC measurements were performed in air using a DSC (TA Instruments Q200), with the temperature scanned from -50 °C to 70 °C at a rate of 10 °C / min. Field emission SEM (IT-500HR) and TEM (JEM-F200) equipped with EDS were used to examine the morphology and composition. 1H-NMR (Bruker BioSpin, Avance III HD400) spectra were used to verify the structure of the ionic elastomer, and 1H-NMR / 19F-NMR (Bruker BioSpin, Avance III HD500) spectra were used to verify the diffusion coefficient using the DOSY process. These analyses were performed at the Chronic and Metabolic Disease Research Center of Sookmyung Womans University. The mechanical properties of the ionic elastomer were evaluated using a uniaxial tensile tester (Mecmeshine, 50 N load cell). Here, an elongation rate of 100 mm / min was applied for the cycle test, and the rate was applied up to 100 mm / min to determine the maximum elongation. For electrochemical analysis, AC impedance spectra were measured using a Bio-logic VPM-300 electrochemical workstation with a frequency range of 0.1–1 MHz and an amplitude of 20 mV.To measure the current at the ionic elastomer-MXene junction, a parametric analyzer (4200A, Keithley) was used to measure the current under various DC bias conditions. The output current was converted to voltage using a resistor, and this voltage was measured using a data acquisition (DAQ) system (USB6211, National Instruments). Additionally, an Arduino program was used to turn on an LED when the output voltage exceeded a specific threshold.
[0107] [Supplementary Explanation 1. XPS Analysis of Ionoelastomer-MXene]
[0108] In X-ray Photoelectron Spectroscopy (XPS), the area under the peak of the spectrum represents the number of photoelectrons emitted from a specific element or chemical state within the sample. The binding energy of these electrons is characteristically determined by the corresponding element and chemical environment. Additionally, the peak area is proportional to the number of detected photoelectrons, which reflects the amount of a specific species within the sample. Therefore, the ratio of the XPS peak areas can theoretically represent the relative concentration (ni) of various species using the following equation.
[0109]
[0110] Here, A1 and A2 represent the calculated peak areas, and S1 and S2 represent the corresponding sensitivity coefficients.
[0111] As shown in Fig. 13, the N 1s X-ray photoelectron spectroscopy (XPS) core-level spectra of the ionoelastomer containing charged MXene and the pure ionoelastomer (ES and AT) were compared. The contributions observed at approximately 402 eV, 400.1 eV, and 399.2 eV in the N 1s spectrum of the ES ionoelastomer are attributed to the N+ peak of the EMIM+ cation, the pyrrole nitrogen, and the aromatic imino nitrogen structures, respectively. When the normalized area of the N+ peak corresponding to the mobile cation (EMIM+) was integrated, the value for pure ES was 0.19, while for ES-PMXene it was 0.29. This indicates that the concentration of mobile ions increased when PMXene was mixed with ES.
[0112] Similarly, the contributions observed at approximately 401.9 eV, 400.3 eV, 399.4 eV, and 398.7 eV in the N 1s spectrum of AT ionoelastomer are attributed to the N+ peak of the SPA- anion, the N- peak of the pyrrole nitrogen / SNS, and the aromatic imino nitrogen structures of the TFSI- anion, respectively. When the normalized N- peak area representing the TFSI- ion was integrated, the value for pure AT was 0.65, while for AT-NMXene it was 0.93. These results verify that the mobile ion concentration increased when NMXene was mixed with AT ionoelastomer.
[0113] [Supplementary Explanation 2. Diffusion-Oriented Spectroscopy (DOSY) and Pulsed Field Gradient] Nuclear Magnetic Resonance (PFG-NMR)
[0114] DOSY and PFG-NMR are advanced nuclear magnetic resonance (NMR) techniques used to measure the diffusion coefficients of molecules or ions within a sample. The core principle of PFG-NMR is to encode spatial information regarding the movement of nuclear spins using short magnetic field gradient pulses. In PFG-NMR, a magnetic field gradient is applied for a very short duration to cause the Larmor frequency of the nuclei within the sample to vary with position. This means that spins experience slightly different magnetic fields depending on their position within the gradient. If molecules diffuse between two gradient pulses, their normal phase changes, resulting in a weaker signal for subsequent spin echoes compared to stationary molecules. The degree of signal attenuation is determined by the magnitude of the molecular displacement, which allows for the quantification of diffusivity.
[0115] To verify the effects of immobilized ion interactions between MXene and ionoelastomers, Diffusion-Oriented Symmetry (DOSY) spectra were collected using NMR on p-type and n-type ionoelastomers, respectively. [EMIM] + and [TFSI] - The self-diffusion coefficient (D) was obtained using the Stejskal-Tanner equation.
[0116]
[0117] Here, S is the PFG-echo profile intensity at the gradient intensity, and γ is the observed nuclear gyromagnetic ratio (26,754 rad s -1 G -1 ), δ represents the gradient duration, and Δ represents the interval between the two gradient pulses.
[0118] When 1 wt% PMXene is mixed into ES, [EMIM] compared to pure ionic elastomer + Diffusion coefficient (D[EMIM] + ) is 4.207 Х 10 -11 From 6.810 X 10-10 It increased to. Similarly, when 1 wt% NMXene was mixed into AT, [TFSI] - Diffusion coefficient (D[TFSI]) - ) is 2.495 X 10 -11 From 3.236 X 10 -11 Increases to [EMIM] within each ionic elastomer + and [TFSI] - This indicates that the mobility of was improved. On the other hand, when NMXene was introduced into ES and PMXene into AT, it was shown that the diffusion coefficient remained almost unchanged compared to the pure ionic elastomer, which can be confirmed in Fig. 14. In the case of ES-NMXene, D[EMIM] + is 3.978 X 10 -11 , in the case of AT-PMXene, D[TFSI] - is 2.595 X 10 -11 It was.
[0119] [Supplementary Explanation 3. Built-in Potential of Ionic Elastomer Junctions]
[0120] We apply a classical thermodynamic model for electronic pn junctions to explain the increase in built-in potential (VB) of ion-elastomer-MXene (ES-PMXene / AT-NMXene) junctions. [EMIM] within ES from a thermodynamic perspective + and AT [TFSI] - It is expected that it will partially dissociate, and the remaining ions will remain bound as a neutral aggregate. This dissociation can be expressed by the following chemical equilibrium equation.
[0121]
[0122]
[0123] The built-in potential of an ion-elastomer junction can be expressed by the following equation.
[0124]
[0125] Here, kB represents the Boltzmann constant, T represents the absolute temperature, and q represents the charge of the particle.
[0126] Experimentally, the VB of the ion-elastomer junction was measured to be approximately 0.2 V, and it was confirmed that adding MXene content to the ion-elastomer increased the VB to approximately 0.4 V (see Fig. 18). We hypothesize that incorporating MXene with surface charge into the ion-elastomer promotes the dissociation of mobile ions via ion-dipole interactions, thereby increasing the binding / dissociation equilibrium constants (KES and KAT) of the ion-elastomer. This phenomenon is similar to the behavior observed in conventional pn junction diodes.
[0127] [Supplementary Explanation 4. Charge Relaxation Time and Changes in Capacitance at Various Temperatures]
[0128] The charge relaxation time (τ = ε / σ = RC) can be determined through a Bode plot obtained by extracting the dominant value in different frequency domains. The charge relaxation frequency (τ) of a parallel RC circuit -1 ) is defined as the frequency at which the imaginary and real impedances intersect in a Bode plot. Therefore, the charge relaxation frequency (τ) -1 ) appears at the cutoff frequency where the real and imaginary impedances cross in the Bode plot. Figure 23 shows the change in the Bode plot at various temperatures. As the temperature increases, the impedance of the junction diode decreases, causing the total impedance plot to shift downward. Additionally, it can be observed that the charge relaxation time decreases. Since it becomes difficult to clearly distinguish between the crossover frequency and the charge relaxation frequency when the temperature exceeds 60°C, the analysis was performed only at temperatures below 50°C.
[0129] Capacitance-frequency measurements of the ion diode can also be performed using impedance spectroscopy, which represents the capacitance value as a function of frequency (see Fig. 24). In the ES-PMXene / AT-NMXene junction diode, the capacitance was higher, particularly in the low-frequency region, compared to the ES / AT junction diode. The capacitance of the junction diode is represented as the sum of the electric double layer (EDL) capacitance and the internal diffusion layer (IDL) capacitance according to the circuit configuration of Fig. 3b. Therefore, this result implies that the capacitances of both the EDL and IDL increased when charged MXene was included. The increase in capacitance is attributed to ion-dipole interactions between PMXene and ES, and between NMXene and AT, which led to an increase in the amount of effective mobile ions. Ultimately, the increase in capacitance resulted in an improvement in the rectification ratio.
[0130] When a forward bias is applied, the IDL existing in the equilibrium state disappears. This forms the EDL capacitance, enabling charge flow. Therefore, as can be seen in Figures 24 and 25, the difference in capacitance (Cfor - Ceq) between the forward bias state and the equilibrium state is related to the charge amount in the forward bias state. On the other hand, in the reverse bias state, since the IDL already exists in the equilibrium state, the change in capacitance is almost the same as in the forward bias state. Charge transfer in the reverse bias state is related to the difference in capacitance (Ceq - Crev) between the equilibrium state and the reverse bias state. Consequently, the ratio (Cfor - Ceq) / (Ceq - Crev) is proportional to the ideal Qfor / Qrev, which represents the ideal rectification ratio. Based on the experimental results, it can be inferred that there is no significant difference in capacitance values between the reverse bias state and the equilibrium state. Therefore, the increase in capacitance in the forward bias state has a significant impact on the improvement of the rectification ratio, which is attributed to the increase in EDL capacitance.
[0131] [Supplementary Explanation 5. Experimental Setup for Voltage Measurement Using DAQ and Arduino]
[0132] To convert the output current of the ion logic gate into voltage, a resistor was integrated into the logic gate output line to comply with Ohm's Law (V = IR). This was measured using a data acquisition (DAQ) system (USB6211, National Instruments) as shown in Fig. 5f. This allowed for more accurate verification of the output value. The variation in the output value was 400 mW / cm². 2 Measurements were taken by applying NIR of varying intensity. When no NIR light was applied to the diode, the output voltage exceeded the threshold only at the (1,1) input stage, depending on the operation of the AND gate. However, after NIR irradiation, the output current exceeded the threshold even at the (1,0) or (0,1) input stages. This caused the diode to operate as an OR gate. Once the heated diode cooled, the operation was restored to that of an AND gate. At this point, the output voltage did not exceed the threshold unless both inputs A and B received a '1' signal. The output value exceeding the threshold ('1') was visually demonstrated using an Arduino and an LED (related video can be found in Supplementary Video 1). This demonstrates the utility of utilizing ionic elastomers and charged MXene composites to create reconfigurable logic gates.
[0133] [Supplementary Explanation 6. Circuit Simulation using LT-SPICE and Falstad]
[0134] An attempt was made to reproduce an NIR-responsive reconfigurable ion logic gate using LT-SPICE (Linear Technology) circuit simulation. A similar voltage pattern was generated as shown in Fig. 5e. As shown in Fig. 30(a), the ion diode in the circuit simulation was created by connecting a resistor and a diode, representing a diode whose resistance changes according to NIR exposure. Since two ion diodes form the logic gate, it was configured as indicated in the figure. The voltage signal of the ion elastomer logic gate (composed of two ion diodes) could be verified using an operational amplifier comparator that distinguishes when the output voltage exceeds a threshold voltage and when it does not. The operational amplifier comparator consists of two inputs: a non-inverting input (V+) and an inverting input (V-). When the voltage of the non-inverting input exceeds the voltage of the inverting input, the operational amplifier outputs a voltage corresponding to the power supply voltage as the output voltage. In this case, the power supply voltage was set to 1.05 V. Additionally, the non-inverting input was connected to the output of the logic gate, and the inverting input was fixed at 0.1 V. When NIR light was not applied to the logic gate, due to the high resistance of the logic gate, when a (1,1) signal was applied to inputs 1 and 2, the non-inverting input became higher than the inverting input (Point 1). This produced an output of 1 V by the positive supply voltage of the operational amplifier (Point 2). Conversely, when a (1,0) or (0,1) signal was applied, the non-inverting input voltage was lower than the inverting input voltage. This caused the output to approach ground by the negative supply voltage. However, when NIR light was applied to the ion elastomer logic gate, the resistance of each diode decreased. Therefore, even when a (1,0) or (0,1) signal was applied, the non-inverting input voltage became higher than the inverting input voltage (Point 1). This produced an output of 1 V (Point 2).This demonstrates the possibility of creating reconfigurable logic gates driven by increased ion mobility as resistance decreases due to NIR. Simulation results obtained using Falstad and LT-SPICE are shown in Fig. 30.
[0135] Although the present invention has been described above with reference to preferred embodiments, those skilled in the art will understand that various modifications and changes can be made to the invention without departing from the spirit and scope of the invention as set forth in the following claims.
Claims
Claim 1 A composite ion-elastomer material with enhanced ion mobility, comprising: an ionoelastomer; and a positively or negatively charged MXene contained within the ionoelastomer that interacts with one of a cation or anion. Claim 2 A composite ion elastomer material with enhanced ion mobility according to claim 1, wherein the mobility of ions having the same charge as MXene in the ion elastomer is enhanced. Claim 3 A composite ion elastomer material with enhanced ion mobility according to claim 1, wherein the ion elastomer comprises one or more materials selected from the group comprising 1-ethyl-3-methylimidazolium (3-sulfopropyl) acrylate ([EMIM][SPA]) and 1-[2-acrylooxyethyl]-3-butylimidazolium bis(trifluoromethane)sulfonamide ([AEBI][TFSI]). Claim 4 In claim 1, the MXene is Ti3C2T x , and Ti3C2T with surfaces treated with polyethyleneimine (PEI) x A composite ion elastomer material with enhanced ion mobility comprising one or more materials selected from the group including Claim 5 An ion elastomer-based diode device with improved ion mobility, comprising: an n-side comprising an ion elastomer; and a negatively charged MXene interacting with a cation contained within the ion elastomer; and an ion elastomer; and a positively charged MXene interacting with an anion contained within the ion elastomer; and a p-side in contact with the n-side. Claim 6 An ion-elastomer-based diode device with improved ion mobility according to claim 5, wherein the diode device further comprises: a first electrode in contact with the n-side; and a second electrode spaced apart from the first electrode and in contact with the p-side. Claim 7 An ion elastomer-based diode device with enhanced ion mobility, wherein the ion elastomer of the n-side comprises one or more materials selected from the group including 1-[2-acrylooxyethyl]-3-butylimidazolium bis(trifluoromethane)sulfonamide ([AEBI][TFSI]). Claim 8 An ion-elastomer-based diode device with enhanced ion mobility, wherein the ion-elastomer of the p-side comprises one or more materials selected from the group including 1-ethyl-3-methylimidazolium (3-sulfopropyl) acrylate ([EMIM][SPA]). Claim 9 In paragraph 5, the MXene included in the n-side is Ti3C2T x An ion-elastomer-based diode device with enhanced ion mobility comprising one or more materials selected from the group including Claim 10 In paragraph 5, the MXene included in the p-side is Ti3C2T with a surface treated with polyethyleneimine (PEI). x An ion-elastomer-based diode device with enhanced ion mobility comprising one or more materials selected from the group including Claim 11 An ion-elastomer-based diode device with improved ion mobility, wherein the MXene included in the n-side or the p-side is included in an amount of 0.5 to 3 wt%. Claim 12 A gate whose characteristics are controlled by light, comprising a diode element including: an n-side comprising an ion elastomer; and a negatively charged MXene interacting with a cation contained in the ion elastomer; and an ion elastomer; and a positively charged MXene interacting with an anion contained in the ion elastomer; and a p-side in contact with the n-side; and further comprising: two or more input electrodes in contact with one of the n-side or the p-side; and an output electrode spaced apart from the input electrode and in contact with the other side. Claim 13 In claim 12, the diode element comprises an ion-elastomer-based diode element with enhanced ion mobility according to any one of claims 5, 7 to 11, and is a gate whose characteristics are controlled by light. Claim 14 In claim 13, a gate whose characteristics are controlled by light, wherein the resistance of the diode element is lowered when light is irradiated. Claim 15 A light control element comprising: a gate whose characteristics are controlled by light; and a light source capable of irradiating light to the gate; wherein the gate comprises a gate according to claim 12.